Random amplified polymorphic DNA (RAPD) analysis of banana - Rajamanickam C (Department of Pomology and Floriculture, College of Agriculture, 2003)
A study entitled "Random Amplified Polymorphic DNA (RAPD) analysis of banana (Musa spp.)" was conducted at the Department of Pomology and Floriculture, College of Agriculture, Vellayani, Thiruvananthapuram during the period from 2001 to 2003. Analysis of the genetic diversity. of some of the banana clones and intra-clones belonging to different genomic groups (AAA, AAB, ABB, AA, AB and BB) and ploidy groups (triploids and diploids), based on morphological traits and RAPD profiles is aimed at. Twenty eight banana clones were used for the study. Clones and intraclones of banana were collected from Banana Research Station (BRS), Kannara; Banana Nursery Farm, Palode, Thiruvananthapuram; Instructional Farm, College of Agriculture, Vellayani and Batlagundu, Tamil Nadu. DNA isolated from the twenty eight banana clones were subjected to RAPD analysis. Out of the forty one decamer primers screened for RAPD analysis, 34 could produce amplification. One hundred and twenty three bands (average: 3.00 bands per primer) were generated by thirty four primers, of which 94.31 per cent (116 bands) were polymorphic. Seven bands (5.69 %) were monomorphic. Twenty five primers showed high level of polymorphism. Finally, six most promising primers viz., OPA-Ol, OPA-03, OPA-13, OPB-04, OPB-IO and OPB-12 were used for RAPD analysis of the twenty eight banana clones. These primers yielded 46 scorable bands with an average of 7.66 bands per pnmer. From the dendrogram, it was found that the twenty eight banana clones clustered into fourteen groups at a distance of 0.200. At a distance of 0.250, 8 out of 12 Nendran (AAB group) intraclones viz., Chengazhikodan, Myndoli, Kaliethan, Vellayani Nendran, Zanzibar, Mysore Ethan, Manjeri Nendran and Changanasseri Nendran formed single cluster. Palayankodan (AAB group) intraclones like, PKNNR, Pisang Ceylon, Motta Poovan, Chandra Bale and Palode Palayankodan formed another single cluster. At a distance of 0.120, Red banana and